Analisis Kenyamanan Termal Ruang Kuliah - Hadi, Yuswono; Azaria, Tabitha; ., Purnomo; Putrianto, Novenda K.; Oktiarso, Teguh; Ekawati, Yurida; Noya, Sunday (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
Bhakti Persada Building is one of the main buildings at Ma Chung University that serves as a place for the lecture process and student activities. Every room of Bhakti Persada Building has an AC that is on every day and there are very adequate windows and vents. The study aims to provide thermal comfort to the space users by measure temperature, humidity, and wind speed before and after the engineering of space facilities using SNI 6390: 2011 for temperature and humidity as well as the MENKES No.261 / MENKES / SK / 11/1998 standard for wind speed. In addition, this study was also conducted by paying attention to environmental issues, especially energy utilization, so that later it will be obtained scheduling to use of air conditioners as well as the efficiency of the use of electrical energy after the engineering of space facilities. The results of thermal comfort analysis after engineering the room facilities, obtained the time zone of the lecture room using a propeller fan is the time zone I and II for all sizes of lecture rooms while for time zone III all lecture rooms will use air conditioning because the temperature increases ± 0, 5 ° C, and for time zone IV lecture rooms with sizes 5 x 9 m, 6 x 9 m and 8 x 9 m the second floor will use a fan and a room size 8 x 9 m and 10 x 9 m third floor will use AC. After the engineering of space facilities, it was also found that the efficiency of the use of electrical energy in the lecture hall of the Bhakti Persada Building was 53%.